A Rare Cause of Abdominal Pain: Superior Mesenteric Artery Branch Pseudoaneurysm Rupture - , Qianqian Li, Yanhong Gao, Hao Yan, Xingshun Qi, Chun Ye (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Li Q, Gao Y, Yan H, Ye C, Qi X. A rare cause of abdominal pain: superior mesenteric artery branch pseudoaneurysm rupture. Turk J Gastroenterol. 2024;35(11):869-871.